2016
DOI: 10.1002/app.44152
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of polylactide in aqueous media

Abstract: In this study, two commercial polylactide (PLA) grades with different d‐lactate contents were subjected to hydrolysis in neutral, acidic, and alkaline aqueous media at temperatures above the glass transition. We monitored the hydrolysis process by means of tracking the changes in the molecular weight distribution, weight loss, water uptake, and PLA crystallinity as a function of time. In both, neutral and acidic media, hydrolysis showed an initial induction period over which no weight loss was observed, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 31 publications
(62 reference statements)
7
52
0
Order By: Relevance
“…The lower polymer chains may be removed from the polymer surface, allowing the biotic process to begin with microorganisms absorb these low M w chains and complete the decomposition of the material. As the hydrolysis is strictly related to water absorption, the lower values of degradation of the samples are associated to the better compatibility in the polymer matrix and to the high orientated amorphous structures, which reduces the free spaces leading to small rates of hydrolysis and consequently reduces degradation rates . The results agrees with outer results, as reported by Palsikowski et al .…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The lower polymer chains may be removed from the polymer surface, allowing the biotic process to begin with microorganisms absorb these low M w chains and complete the decomposition of the material. As the hydrolysis is strictly related to water absorption, the lower values of degradation of the samples are associated to the better compatibility in the polymer matrix and to the high orientated amorphous structures, which reduces the free spaces leading to small rates of hydrolysis and consequently reduces degradation rates . The results agrees with outer results, as reported by Palsikowski et al .…”
Section: Resultssupporting
confidence: 91%
“…Table shows the mass variation behavior for 360 days, period when they were inserted into the simulated soil. In the initial phase, the mass of all samples slightly increased, as expected, due to the water absorption on it . However, after the analyzed period, the samples did not present an expressive mass reduction (with only a slight reduction observed after 270 days).…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Several studies have investigated the kinetics of PLA hydrolysis . Based on our previous work, an exponential model of the drop in molecular weight over time can be successfully described by two‐stage: Mn=true{leftMn01ek1t if t<tPMn02ek2t if t>tP where M n 01 is the molecular weight prior to hydrolysis, M n 02 is the molecular weight intercept of the second hydrolysis stage, k 1 as well as k 2 are the kinetic constants for each stage, and t P is the time where the shift occurs between the two stages. The first stage, was called the induction period and was characterized by a dramatic drop in molecular weight without any weight loss.…”
Section: Introductionmentioning
confidence: 99%
“…found for thin amorphous PLA films in an alkaline medium that the crystallinity increased only by 8% after 150 days. At higher temperatures, above T g , it was found that PLA crystallinity increases to its maximum level within 24 h …”
Section: Introductionmentioning
confidence: 99%